Prevalence of Attention Deficit Hyperactivity Disorder Among Students with Learning Disabilities - Huda Al-Shekaili; Fatema AlMalki; Zubaida Shebani; Muna Al-Bahrani; Suhail Al-Zoubi (Emerging Science Journal, 2025)
Attention deficit hyperactivity disorder (ADHD) is a common developmental disorder worldwide, occurring among children and adolescents across cultures and societies. ADHD manifests itself in difficulties with concentration, distraction, hyperactivity, and impulsive behavior. ADHD poses a challenge in school settings, affecting students' ability to follow lessons, adhere to instructions, and complete academic tasks. Omani schools are witnessing cases of ADHD, which calls for educational and health attention to develop effective strategies to reduce the prevalence of ADHD among school students. Therefore, this study aimed to identify the prevalence of Attention Deficit Hyperactivity Disorder (ADHD) among Omani students with learning disabilities (LDs). A descriptive survey design was employed, with a sample of 861 students with LDs from different governorates in Oman. To assess ADHD symptoms, a standardized scale was developed based on the criteria outlined in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5). The final version of the scale comprised 25 items distributed across two core domains: Inattention and Hyperactivity/Impulsivity. Findings revealed that 28% of students with LDs met the criteria for ADHD, with Inattention being the predominant subtype (58%). ADHD was more prevalent among male students (73%) and was most commonly observed in students in grades 1-4 (75%). Additionally, 63% of ADHD cases were identified in students with Arabic language difficulties, particularly in reading and writing. The study highlights the need for systematic ADHD screening among students with LDs and recommends the adoption of the developed scale for early identification and intervention.